Urban, Agricultural and Livestock Residues in the Context of Biorefineries - Gómez-Soto, James Andrés; Sánchez-Toro, Óscar Julián; Matallana-Pérez, Luis Gerónimo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The generation of waste is increasing globally and its poor utilization causes serious environmental, economic and social issues. The aim of this work was to analyze the state of the art on urban, agricultural and livestock solid waste in terms of quantity and composition, as well as to analyze the concept of biorefineries from the viewpoint of their design as a sustainable alternative for the use of residual raw materials. The information was consulted in different databases such as Web of Science, Scopus, and Google Scholar. The analysis of the information identified that the residues are produced in considerable amounts and have valuable organic compounds, which are used to a greater or lesser extent according to technological, cultural, and socio-economic factors in each specific region. New policies are needed for the integral management of solid waste that integrates the concept of biorefineries from the generation and separation at the source to its utilization and final disposal. The proper implementation of physical, thermochemical, chemical, and biological processes under the concept of biorefineries can recover or transform in an integral way the residual raw materials to obtain products such as biofuels, food, and energy. Designing biorefineries to determine their viability for waste utilization is required. Exploring this type of alternatives by evaluating different factors (techno-economic, environmental, and social) may support the decision making of investment and research in utilization technologies to be implemented on a small or large scale in regions of Colombia and the world with great waste availability.